Supportive psychotherapeutic intervention and video directing observed therapy to increase family adherence - Supratti, Supratti; Zees, Rini Fahriani; Gobel, Hafni Van; Adam, Lusiane; Luawo, Herman Priyono (Intelektual Pustaka Media Utama, 2024)
To determine the effect of supportive psychotherapy and video-directing observed therapy interventions on family compliance in assisting patients with mental disorders in the working area of the Kabila Health Center, Bone Bolango District, Gorontalo City. Research design quasi-experimental design with a one group pre- and post-test design, where the variables to be measured are family adherence in providing treatment assistance, which are included in the dependent variable. The independent variables in this study were supportive psychotherapy and video-directed observation therapy. The sampling technique used was a total sampling technique with a sample size of 39 respondents. Data analysis was performed using univariate analysis, namely descriptive analysis (frequency, percentage, median, minimum value, and maximum value) and bivariate analysis (Wilcoxon test), with a significance level of <0.05, which was performed using SPSS version 25 software. Supportive psychotherapy and video-directing observed therapy increased family compliance accompanying the treatment of patients with mental disorders (p-value of x1=0.020, x2=0.000, p<0.05). Supportive psychotherapy interventions and video-directed observed therapy have been proven to increase family compliance in treatment assistance, which can improve the quality of life of patients with mental disorders.